2017
DOI: 10.11648/j.ajns.20170605.13
|View full text |Cite
|
Sign up to set email alerts
|

Factors Affecting Nurses’ Compliance in Preventing Pressure Ulcer Among Hospitalized Patients at King Abdulaziz University Hospital

Abstract: Prevention of pressure ulcers is an indicator of quality of care. Nursing care has a major effect on pressure ulcer development and prevention. Hence, many people believe that most pressure ulcers are preventable if the appropriate interventions are implemented. The study aimed to assess factors affecting nursing compliance in preventing pressure ulcer. Descriptive correlation design was used which is a type of non-experimental design to collect data from medical, surgical units and the critical cardiac unit a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 24 publications
(29 reference statements)
2
3
1
Order By: Relevance
“…In an attempt to identify barriers to applying preventive bundle guidelines among nurses in the current study, nurses attributed to lack of up-to-date knowledge, high workload and insufficient equipment were the common barriers. These results are in congruence withAl-Ghamdi, (2017) 37 who conducted a study to assess factors affecting nurses' compliance in preventing pressure ulcer and found that,heavy workload/staff shortage is considered as the most barriers facing nurses" compliance regarding prevention pressure ulcer. Moreover, this finding is similar to Mwebaza, et al, (2014) 38 who assess nurses' knowledge, practices, and barriers in care of patients with pressure ulcers in a Ugandan teaching hospital and found that, shortage of supplies, resources and lack of training were the most barriers to carrying out appropriate pressure ulcer management.…”
Section: Discussionsupporting
confidence: 87%
“…In an attempt to identify barriers to applying preventive bundle guidelines among nurses in the current study, nurses attributed to lack of up-to-date knowledge, high workload and insufficient equipment were the common barriers. These results are in congruence withAl-Ghamdi, (2017) 37 who conducted a study to assess factors affecting nurses' compliance in preventing pressure ulcer and found that,heavy workload/staff shortage is considered as the most barriers facing nurses" compliance regarding prevention pressure ulcer. Moreover, this finding is similar to Mwebaza, et al, (2014) 38 who assess nurses' knowledge, practices, and barriers in care of patients with pressure ulcers in a Ugandan teaching hospital and found that, shortage of supplies, resources and lack of training were the most barriers to carrying out appropriate pressure ulcer management.…”
Section: Discussionsupporting
confidence: 87%
“…This may be because women worry more about their children, which raises their stress levels and can make them more likely to experience PPD. By contrast, the presence of any maternal chronic illness did not affect PPD rates in this study, contrary to the study by AlGhamdi et al [55].…”
Section: Partner Abuse and Ppdcontrasting
confidence: 99%
“…A woman's overall mental health history and a history of traumatic or stressful experiences may also put her in a bad mood. Additionally, similar to the findings of AlGhamdi et al, women who experienced pregnancy problems and whose newborns required intensive care unit care had a greater incidence of PPD than those who did not [55]. This may be because women worry more about their children, which raises their stress levels and can make them more likely to experience PPD.…”
Section: Partner Abuse and Ppdsupporting
confidence: 65%
“…In this study availability of sufficient pressure-relieving devices or equipment was an independent predictor for nurse's pressure ulcer prevention practice. This is supported by different studies which found that Scarcity of pressure reliving equipment was the identified factors which limit nurses' practice of pressure ulcer prevention [16,31,32]. This might be due to the fact that adequate access to sufficient equipment may encourage nurse's motivation and ability to prevent patients from developing pressure ulcer.…”
Section: Plos Onementioning
confidence: 80%